PENINGKATAN DOMAIN KOMPETENSI DAN PENGETAHUAN SISWA MELALUI PENERAPAN LEVELS OF INQUIRY DALAM PEMBELAJARAN IPA TERPADU - Puspo Rohmi (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2017)
Abstract The aim of this study was to determine the enhancement of students’ competencies and knowledge domains of scientific literacy after the levels of inquiry on integrated science instruction was implemented on the theme of environmental pollution. This study used pre-experimental research method with one sample pretest-posttest design. Data were collected through scientific literacy test, observation sheet, worksheet, and questionnaire instruments. Wilcoxon Signed Ranks test results showed that there was a statistically significance different between the pretest scores and the posttest scores after implementing levels of inquiry. Significance is shown by both domains of competencies and knowledge aspects studied. Results indicated that the implementation of levels of inquiry in integrated science lesson can enhance students' scientific literacy on competencies and knowledge aspects. It was concluded that implementing the levels of inquiry can help students to practice inquiry skills to enhance their scientific literacy which requires the application of competencies and knowledge they have. In addition, it was also found that the students’ have positive response about using inquiry systematically in science instruction. Keywords: levels of inquiry; scientific literacy; competencies domain; knowledge domain; integrated science Abstrak Penelitian ini bertujuan untuk mengetahui peningkatan domain kompetensi dan pengetahuan siswa setelah diterapkannya levels of inquiry pada pembelajaran IPA terpadu tema pencemaran lingkungan. Penelitian ini menggunakan metode penelitian pre-eksperimental dengan desain one-sample pretest posttest design. Instrumen yang digunakan untuk mengumpulkan data adalah tes literasi sains berbentuk pilihan ganda, lembar observasi, dan angket. Hasil analisis data tes literasi sains menggunakan uji Wilcoxon Signed Ranks menunjukkan bahwa terdapat perbedaan yang signifikan antara skor pretes dan skor postes setelah diterapkannya levels of inquiry. Sebagai kesimpulan yaitu penerapan levels of inquiry dapat membantu meningkatkan domain kompetensi dan pengetahuan siswa pada pembelajaran IPA. Hasil penelitian ini juga menunjukkan bahwa siswa mempunyai respon positif terhadap penggunaan inkuiri yang dilakukan secara sistematis dalam pembelajaran IPA. Kata Kunci: levels of inquiry; literasi sains; domain kompetensi; domain pengetahuan; IPA terpadu Permalink/DOI: http://dx.doi.org/10.15408/es.v9i1.1979